2001
DOI: 10.1007/s005950170070
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Death in Renal Transplant Patients: A Comparison Between Azathioprine and Ciclosporin

Abstract: The results of renal transplantation have improved due to advances in immunosuppression techniques of preservation, and pre- and postoperative treatments; however, both morbidity and mortality remain serious problems. To decrease the morbidity and mortality rates we analyzed the causes of death after renal transplantation in our hospital. Between 1972 and 1999, we performed 364 renal transplantations, 257 of which were living-related and 107, cadaveric. There were 178 patients given azathioprine and 186 given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…[2] Immunosuppressive therapy, which is necessary to avoid premature graft loss, increases the tendency to atheroma. Tacrolimus, cyclosporine (to a greater degree than tacrolimus), and corticosteroids have been implicated in post-transplant hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Immunosuppressive therapy, which is necessary to avoid premature graft loss, increases the tendency to atheroma. Tacrolimus, cyclosporine (to a greater degree than tacrolimus), and corticosteroids have been implicated in post-transplant hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, post-transplant cardiac complications increase the morbidity and mortality rates after renal transplantation. [2] Cardiovascular disease is the leading cause of death in renal transplant patients accounting for 40-55% of all deaths, and the incidence is considerably higher than in the general population. [3] The main contributing factors leading to atheroma include older age, male gender, hyperlipidemia, smoking, obesity, lack of exercise, hyperglycemia, and hyperhomocysteinanemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific immunosuppressants have been reported to alter the risk for certain types of cancers. Azathioprine is associated with an increased risk of anogenital, lip, and skin cancers, [27] increasing the risk of the latter by 17%. [25] Tacrolimus, on the other hand, has been associated with a 35% decreased risk of skin cancers compared with other immunosuppressants.…”
Section: Malignancymentioning
confidence: 99%
“…CVD has been attributed to be the most common cause of death followed by infection and then malignancy [15,74]. Some studies have, however, reported infections as a major cause of death [75,76]. Older age, being a risk factor for hypertension, diabetes mellitus [77] and coronary artery calcification [78], puts the older recipients at high risk of CVD.…”
Section: Patient and Graft Outcomesmentioning
confidence: 99%